Determinants of Consumer Preference On Ride-Hailing Platforms In South-East Asia - Donant Alananto Iskandar; Triyono Arief Wahyudi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This research is an associative quantitative type that discusses the influence of variables that determine customer choices for online transportation services in Indonesia and Singapura. The object of this study is people who have used the application and used online transportation services at least 3 (three) times since the study began, that is November 2019 to October 2020 in Indonesia and Singapura. The data analysis method used is a statistical test using the SPSS and AMOS programs, i.e. tests of normality, validity, reliability, classic assumptions, hypotheses, determination, simple regression, ANOVA, multiple regression, HRA and MRA to see the effect of independent and moderating variables whether to strengthen or weaken the dependent variable.